Peran Yayasan Jayapangus Dalam Mengembangkan Potensi Kearifan Lokal Dusun Siladan Untuk Mendukung Bangli Sebagai Kota Wisata - Anak Agung Gde Raka; Anak Agung Ayu Dewi Larantika; I Gusti Ayu Dian Susanti (Postgraduated Community Service Journal, 2020)
Dusun Siladan is located in Taman Bali Village, in about seven minutes it has arrived at the city center. Natural conditions and the environment still look beautiful, because tourism activities have not been touched. The potential of the hamlet is very suitable to be developed as a supporter of Bangli in realizing Bangli as a tourism city, in order to complement Penglipuran Village as a tourist attraction. Penglipuran Village, which is known as one of the cleanest villages in the world, does not seem to have local products to support tourism, both in the form of entertainment and souvenirs. For this reason, the presence of the Jayapangus Foundation has the potential to be empowered, both as a provider of entertainment and souvenir services. To find out and understand the potential of Siladan hamlet, we used the observation method to observe people's attitudes and behavior and the interview method with a purposive system, namely interviewing several local community leaders, then supplemented with a literature study. The data that has been collected is processed and analyzed using a qualitative descriptive analysis method.